Vegetation restoration has an implication for fungal diversity and composition in a degraded temperate desert type rangeland of China - Zhou, Xuanbo; Wang, Xiaoli; Wang, Yanlong; Ma, Yuan; Liu, Ying; Ma, Yushou (Ecological engineering, 2024)
The degradation of temperate desert type rangeland leads to decreased vegetation diversity and soil nutrients levels. Grazing prohibition and artificial revegetation are common strategies for vegetation restoration. However, it is currently unknown the duration of grazing prohibition and artificial revegetation affect soil microorganisms. Therefore, experiments on grazing prohibition duration and artificial revegetation were conducted to explore the response of soil microorganisms to these measures. Field experiments were conducted during the peak plant growth season in Guide County, China, to evaluate methods involving grazing prohibition and artificial revegetation. We established six experimental sites, which were grazing prohibition for fifteen years (P15), grazing land located near P15 (P15-CK), grazing prohibition for eight years (P8), grazing land located near P8 (P8-CK), artificial revegetation for three years (A3), and wasteland located near A3 (A3-CK). The results showed that artificial revegetation measures decreased the plant diversity, whereas grazing prohibition for eight years increased it. Artificial revegetation and grazing prohibition measures led to an increase in pH and total carbon, and a decrease in total nitrogen and total phosphorus. The amount of total PLFA increased with artificial revegetation, whereas grazing prohibition resulted in a decrease of total PLFA. Artificial revegetation and grazing prohibition measures decrease the relative abundance of the Ascomycota phylum and the fungal diversity. In addition, the study found that fungal communities were primarily influenced by soil factors such as ammonium nitrogen, pH, and total carbon, rather than by plants. Vegetation restoration enhances the accumulation of total soil carbon and alters fungal community composition and diversity. The effects of artificial revegetation and grazing prohibition measures on the amount of total PLFA varied. These findings provide important information that vegetation restoration promotes soil nutrient accumulation but reduces fungal diversity, which can inform the restoration of degraded temperate desert type rangeland. •National parks as research subjects, which save the cost and time.•Each of the three treatments has its own control group, which reduces error.•Choice of native vegetation of Asterothamnus centraliasiaticus.•Interactions between vegetation, soil, and microorganism.